2021
DOI: 10.1111/pops.12770
|View full text |Cite
|
Sign up to set email alerts
|

Taking Care of Each Other: How Can We Increase Compliance with Personal Protective Measures During the COVID‐19 Pandemic in Chile?

Abstract: In the context of the COVID‐19 pandemic, personal protective measures (e.g., social distancing, handwashing, and mask wearing) have been adopted as a cornerstone to limit the spread of the disease. Yet, the effectiveness of these measures depends on people's levels of adherence. In this article, we apply social‐psychological research to the study of compliance with personal protective measures during the COVID‐19 pandemic in Chile. We consider three possible models underlying adherence: (1) sociodemographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 53 publications
4
25
0
3
Order By: Relevance
“…Similarly, Lee and Li [ 3 ] have found that subjective norms were the most influential determinants of social distancing behavior and significantly mediated the relationship between trust and this behavior. In addition, these results are similar to other studies carried out in Chile, which indicate that the opinion and behaviors of friends and relatives are relevant for young people to carry out preventive behaviors against Covid-19 [ 57 ]. Then, our results suggest aspects of the Chilean culture and how social relationships are built that can favor decision-making in uncertain and ambiguous situations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, Lee and Li [ 3 ] have found that subjective norms were the most influential determinants of social distancing behavior and significantly mediated the relationship between trust and this behavior. In addition, these results are similar to other studies carried out in Chile, which indicate that the opinion and behaviors of friends and relatives are relevant for young people to carry out preventive behaviors against Covid-19 [ 57 ]. Then, our results suggest aspects of the Chilean culture and how social relationships are built that can favor decision-making in uncertain and ambiguous situations.…”
Section: Discussionsupporting
confidence: 88%
“…For example, a study of vaccination behavior in Latin America identified fear as one of the most influential predictors of the intention to be vaccinated [ 43 , 44 ]. Similar results were reported in a study associated with the A (H1N1) influenza pandemic conducted in the Netherlands [ 30 ], Italy [ 29 ], Hong Kong [ 31 ], the United States [ 56 ], and France [ 57 ]. In the SARS-CoV-2 virus pandemic context, high levels of worry and fear were associated with increased adoption of protective behaviors [ 6 , 9 ].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are also coherent with the social amplification of risk literature because others have a role in determining what risk is and how to act accordingly—in this case, through vaccination. Thus, those who have shown greater concern for collective norms and the self (collectivism), prioritizing the sense of social responsibility, have shown greater adherence to different healthcare behaviors to avoid COVID-19 infection [ 62 ]. These findings become relevant in Latin American countries, in which “significant others” such as family and friends have a transcendental role in decision making and behaviors (e.g., familism, a characteristic of Latin and Asian cultures that involves the prioritization of the family over the self; see Schwartz and Weisskirch [ 63 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Another paper provides evidence that that family, community, and national identification has significant links with self-reported helping and physical distancing, and provides an example of good health messaging around these topics ( Vignoles et al, 2021 ). Similarly, public health messages around protecting us are more powerful than protecting oneself ( Wang and Lee, 2020 ; Gerber et al, 2021 ), as these messages can build trust between ethnic groups and governments ( Razai et al, 2021 ).…”
Section: How To Reduce Blame In a Pandemicmentioning
confidence: 99%